Learning Strategies on Islamic Religious Values in Children Aged 4-5 Years - Adityasari, Pramitha; Elfitasari, Tita (Universitas Negeri Semarang, 2014)
Children age 4-5 years are on the fairy tale stage that the way they absorb religious values is still influenced by fantasy and emotion. Religion values development of children in Siti Sulaechah 04 Pre-school and Kindergarten Semarang is developing well because learning Islamic values conducted intensively in religion class. This study aims to describe the implementation of learning strategies on Islamic values and the factors that influence it. This study used qualitative research methods. Data collection technique used in this study were observation, interview, and documentation. The method used to test the validity of data was method and source triangulation technique. The data analysis used data reduction, data presentation, conclusion and verification. The results showed that learning strategies on Islamic values in Siti Sulaechah 04 Pre-school and Kindergarten Semarang included lesson planning, organizing strategies, delivery strategies, and management strategies. Lesson planning included yearly programme, semester programme, weekly lesson plan, and daily lesson plan. Organizing strategies included sequencing and synthesizing. For the delivery strategies, the teacher used and utilized teaching media, and doing learning activities with classical and individual models. The management strategies used were teaching methods, making study progress notes, and giving motivation. There are six factors which influenced teachers in implementing those four learning strategies, they are children development, basic competence (indicators), teaching materials, the time allocated, learning facilities, as well as the ability of teachers to implementation learning strategies.How to citeAdityasari, P., & Elfitasari, T. (2014). Learning Strategies on Islamic Religious Values in Children Aged 4-5 Years. Indonesian Journal of Early Childhood Education Studies, 3(2), 79-83. doi:10.15294/ijeces.v3i2.10064DOI 10.15294/ijeces.v3i2.10064